Spirometric studies in children, with special reference to asthma - Heese, Hans de Villiers (Department of Paediatrics and Child Health, 2017)
This thesis is a report on the value and limitations of the practical application of the Forced Expiratory Volume and Forced Vital Capacity test in children aged from 7 to 16 years. The first part deals with review of the literature on lung function and evolution of the Forced Expiratory Volume and Forced Vital Capacity test. The method and apparatus used in the test, the establishment of "normal values", the correlation of these values and certain anthropometric data, the establishment of prediction formulae for normal values, a study of the effect of factors such as sex, "learning" and repeatability, posture, daily and day-to-day variations, and the inhalation of isoprenaline on these normal values are reported. The second part deals with the practical application of the test in various pathological conditions affecting the cardio-respiratory system. The effect of respiratory disorders on ventilatory function is reported and an attempt is made to assess the effect of management, medical treatment and prognosis of a respiratory disorder at any given stage of that disorder acknowledging always that the complete evaluation of a patient requires more than laboratory tests.